Efficacy of Intelligent Mosquito System (I.M.O.S) with Xmos mini aerosol against Aedes in 17th College, Universiti Putra Malaysia - Saiful Yazan, Latifah; Gopalsamy, Banulata; Abu Bakar, Siti Najiha; Manan, Khairul Aiman; Shahidan, Noranis Shahida; Lee, Yean Wang (Universiti Putra Malaysia Press, 2021)
This study reports the efficacy of I.M.O.S (Intelligent Mosquito System) by using Xmos mini aerosol in reducing Aedes mosquito population in 17th College, Universiti Putra Malaysia (UPM). Prior to the experiment, the Aedes mosquito population was determined in all blocks of the 17th College, UPM. The I.M.O.S. was installed above the entrance door of the hall and two rooms and was set to automatically spray at 6.30 am and 4.00 pm every day. No intervention was used in the control house. Adult efficacy study was conducted by placing 20 Aedes mosquitoes in each cage and was hung at a distance of 10 feet from the I.M.O.S. The mortality caused by I.M.O.S throughout the exposed two hours and after 24 hours of exposure was recorded. The number mosquito eggs population were calculated throughout the installation of I.M.O.S. Data were analysed using two-way ANOVA and paired T-test, respectively. The mean number of Aedes mosquito eggs and ovitraps index showed no significant difference (p>0.05) between control and treatment blocks. There were significant differences (p<0.05) in the percentage of knockdown of adult Aedes mosquitoes (10, 20, 30, 60 and 120 minutes after exposure) and the mortality of adult Aedes mosquitoes after 24 hours exposure. Nano and slow-release technology of the I.M.O.S with Xmos mini aerosol proved that this type of intervention can kill adult Aedes mosquitoes. Thus, it is a potential intervention for vector control and management.